The Conceptual Framework for Water Accounting in Sustainability of Peatland Ecosystems. An Islamic Perspective - IRFAN, Andi; FEBRIA, Dessyka; NOFIANTI, Leny; RIJULVITA, Silva (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.v11.3(43).11, 2020)
Water accounting is a new topic that discusses the impact of environmental changes where the existence of water as one of the most vital natural resources is becoming increasingly scarce. The conceptual framework of water accounting should include the element or value of Ihsan. That is, it is expected that users will be able to implement the Ihsan value in water accounting. The environment is an ecosystem created entirely by God for human life. The value of Ihsan in the conceptual framework of water accounting, especially peatland, requires knowledge of the characteristics, types and distribution of peatland. It is intended that peatland can be utilized and managed sustainably. Implementation of the Ihsan value of utilizing peatland for life without damage. As khalifatullahfilard , humans must be able to maintain a balanced environment and life so that nature remains sustainable.